Loss Mechanisms of Optical Cables Used in Communication Lines (Eurasian Journal of Engineering and Technology, 2023)
In this work, the mechanisms of optical loss in fiber were considered. The mechanisms of special infrared (IR) and ultraviolet (UV) absorption were considered, and the technical characteristics of optical fibers used in communication lines were considered. It analyzed mainly the types, properties of optical fiber, the predominance of fiber optic cable and the losses in fiber optic cables used in communication lines. The results of measuring the signal attenuation in the line of the users using the optical communication line, the signal absorption depending on their line distance and the number of connections in the line were obtained using a reflectometer device.